GaN-based MIS-HEMTs with Al2O3 dielectric deposited by low-cost and environmental-friendly mist-CVD technique. (16th February 2021) - Low, Rui Shan; Asubar, Joel T.; Baratov, Ali; Kamiya, Shunsuke; Nagase, Itsuki; Urano, Shun; Kawabata, Shinsaku; Tokuda, Hirokuni; Kuzuhara, Masaaki; Nakamura, Yusui; Naito, Kenta; Motoyama, Tomohiro; et al.
Abstract: We report on the fabrication and characterization of AlGaN/GaN metal-insulator-semiconductor (MIS) capacitors and high-electron-mobility transistors (MIS-HEMTs) using a 5 nm thick Al2 O3 dielectric deposited by cost-effective and environmental-friendly mist chemical vapor deposition (mist-CVD) technique. Practically hysteresis-free capacitance–voltage profiles were obtained from the fabricated two-terminal MIS-capacitors indicating high quality of the mist-Al2 O3 /AlGaN interface. Compared with reference Schottky-gate HEMTs, mist MIS-HEMTs exhibited much improved performance including higher drain current on-to-off ratio, much lower gate leakage current in both forward and reverse directions and lower subthreshold swing. These results demonstrate the potential and viability of non-vacuum mist-CVD Al2 O3 in the development of high-performance GaN-based MIS-HEMTs.